2018
DOI: 10.3390/inorganics6030078
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Catalyzed Degradation of Cellulose in Ionic Liquid Media

Abstract: Biomass conversion to 5-hydroxymethylfurfural (HMF) has been widely investigated as a sustainable alternative to petroleum-based feedstock, since it can be efficiently converted to fuel, plastic, polyester, and other industrial chemicals. In this report, the degradation of commercial cellulose, the isomerization of glucose to fructose, and the conversion of glucose to HMF in 1-butyl-3-methylimidazolium chloride ([BMIM]Cl]) using metal catalysts (CrCl3, ZnCl2, MgCl2) as well as tungsten and molybdenum oxide-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Compared to water, which generally causes the leaching of the active sites, ionic liquid (1-butyl-3-methylimidazolium chloride) as a solvent effectively converts cellulose to glucose, fructose, and HMF over WO x -and MoO x -based polyoxometalates. 218 The reaction follows cellulose conversion to glucose, epimerization of glucose to mannose, and then dehydration to HMF with an overall product yield of 28.6%. The results were not influenced by decreasing the cellulose loading.…”
Section: Dehydration and Oxidative Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to water, which generally causes the leaching of the active sites, ionic liquid (1-butyl-3-methylimidazolium chloride) as a solvent effectively converts cellulose to glucose, fructose, and HMF over WO x -and MoO x -based polyoxometalates. 218 The reaction follows cellulose conversion to glucose, epimerization of glucose to mannose, and then dehydration to HMF with an overall product yield of 28.6%. The results were not influenced by decreasing the cellulose loading.…”
Section: Dehydration and Oxidative Dehydrationmentioning
confidence: 99%
“…The solid catalysts with strong acid sites showed good reusability for seven cycles without much loss in catalytic activity. Compared to water, which generally causes the leaching of the active sites, ionic liquid (1-butyl-3-methylimidazolium chloride) as a solvent effectively converts cellulose to glucose, fructose, and HMF over WO x - and MoO x -based polyoxometalates . The reaction follows cellulose conversion to glucose, epimerization of glucose to mannose, and then dehydration to HMF with an overall product yield of 28.6%.…”
Section: Catalytic Applications Of Supported Moo X and Wo X Solid A...mentioning
confidence: 99%
“…The ability of the polyoxometalates to convert glucose to 5-hydroxymethylfurfural remained 28.6% lower compared to the yield obtained with CrCl 3 . 106 In another work, the one-step conversion of cellulose to HMF (5hydroxymethylfurfural), an important renewable biofuel precursor and a useful building block, has been achieved in the presence of metal chlorides (CrCl 3 , CuCl 2 , SnCl 4 , WCl 6 ) in [C 4 mim]Cl (Scheme 3). 107 These trials highlight the ability of ionic liquids to dissolve high molecular weight cellulose and to promote controlled cellulose degradation reactions.…”
Section: ■ Cellulose As a Sustainable Resource For The Formation Of M...mentioning
confidence: 99%
“…For example, Aid et al showed that tungsten and molybdenum oxide-based polyoxometalates are able to decompose cellulose to carbohydrates such as glucose and mannose and a certain amount of glucose was also converted to 5-hydroxymethylfurfural. The ability of the polyoxometalates to convert glucose to 5-hydroxymethylfurfural remained 28.6% lower compared to the yield obtained with CrCl 3 . In another work, the one-step conversion of cellulose to HMF (5-hydroxymethylfurfural), an important renewable biofuel precursor and a useful building block, has been achieved in the presence of metal chlorides (CrCl 3 , CuCl 2 , SnCl 4 , WCl 6 ) in [C 4 mim]Cl (Scheme ).…”
Section: Cellulose As a Sustainable Resource For The Formation Of Mol...mentioning
confidence: 99%
“…In addition, POMs have strong tolerance to impurities, and the reduced POMs can be re‐oxidized and regenerated on simple graphite electrodes, with low energy consumption and huge economic benefits [19,20] . However, the solid biomass with complex networks of polymeric components, especially the hydrogen bond network of cellulose, remained as the highly challenging bottle neck to hydrolytic and oxidative degradation, thus limiting the overall electrochemical reaction rate [21] …”
Section: Introductionmentioning
confidence: 99%